2022
DOI: 10.3390/life12030347
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Coronary Intervention versus Coronary Artery Bypass Grafting for Non-Protected Left Main Coronary Artery Disease: 1-Year Outcomes in a High Volume Single Center Study

Abstract: Introduction: There is clear evidence of a significant reduction in all major cardiovascular adverse events (MACE) by coronary artery bypass grafting (CABG) in left main coronary artery stenosis (LMCS), but revascularization by percutaneous coronary artery intervention (PCI) shows an increasingly important role as an alternative to CABG. Several recent trials aiming to test the difference in mortality between the two types of revascularization found conflicting data. The aim of this study is to determine wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…The chosen revascularization strategies were intended to provide the optimal revascularization for each patient. A logistic Euro SCORE was used to evaluate each patient's risk of surgical complications, with a score of indicating a high likelihood of problems [8][9][10]. The most current iteration of DES was used in each PCI scenario.…”
Section: Study Populationmentioning
confidence: 99%
“…The chosen revascularization strategies were intended to provide the optimal revascularization for each patient. A logistic Euro SCORE was used to evaluate each patient's risk of surgical complications, with a score of indicating a high likelihood of problems [8][9][10]. The most current iteration of DES was used in each PCI scenario.…”
Section: Study Populationmentioning
confidence: 99%
“…Over time, improvements in bifurcation methods and stent quality have allowed us to intervene in LMS disease. In patients with substantial ULMCA stenosis, various studies have shown that PCI to ULMCA with DES is efficacious with favourable in-hospital and in long run results[6].In addition, patients with left main stenosis now have better results due to improved operator expertise, superior physiological assessment and imaging modalities[7].…”
mentioning
confidence: 99%